2019
DOI: 10.1172/jci.insight.98601
|View full text |Cite
|
Sign up to set email alerts
|

Cxcr3-expressing leukocytes are necessary for neurofibroma formation in mice

Abstract: macrophage subpopulations with distinct activities (24,25). Further characterization of these neurofibroma leukocytes and their contributions to tumor initiation and growth is necessary for the development of safe and effective immunomodulatory therapies.In the Dhh-Cre Nf1 fl/fl mouse neurofibroma model, biallelic deletion of Nf1 in the Schwann cell lineage mimics the biallelic loss of NF1 in human NF1 and sporadic plexiform neurofibroma (26). The peripheral nerves of these mice appear normal at 1 month of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…In a few reports, immunological profiling of NF1-associated tumors was analyzed. These investigations potentially offer a way to guide the rational selection of immunotherapeutic treatments (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In a few reports, immunological profiling of NF1-associated tumors was analyzed. These investigations potentially offer a way to guide the rational selection of immunotherapeutic treatments (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In the Nf1 fl/fl ;Dhh Cre neurofibroma mouse model, Cre recombinase is expressed from Desert Hedgehog (Dhh) regulatory sequences to effect recombination of the Nf1 fl/fl allele, resulting in loss of both Nf1 alleles in developing SCPs at E12.5 ( Wu et al, 2008 ). Nf1 fl/fl ;Dhh Cre mice develop paraspinal neurofibromas that have loss of axon-SC interaction in Remak bundles, mast cell and macrophage accumulation, and nerve fibrosis, all characteristics of human PNs ( Wu et al, 2008 ; Liao et al, 2018 ; Fletcher et al, 2019a ; Fletcher et al, 2019b ). In this setting, PNs are present by 4 months of age, and neurofibromas enlarge as the mice age, ultimately compressing the spinal cord causing paralysis and thus, necessitating sacrifice ( Wu et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, since macrophages are recruited via CXCL10-CXCR3, which are expressed in T cells and dendritic cells, the deletion of CXCR3 may prevent neurofibroma formation. However, studies revealed that anti-CXCR3 did not reduce the tumor size of the established tumor [58].…”
Section: Targeting Microenvironmentsmentioning
confidence: 93%
“…All genetically engineered models can be also modified by crossing them with mice that have specific genetic defects to assess the contribution of specific genes on the NF1related tumors in tumor cells or their microenvironments [58,76,91]. Apart from commonly used mice models, scientists also developed a minipig model for NF1 which may overcome some limitations in mouse models and better represent disease features in humans [158,159].…”
Section: Genetically Engineered Models For Nf1mentioning
confidence: 99%